DAMPAK SUSU FORMULA TERHADAP KESEHATAN BAYI - Hanum, Yusfa; Tukiman, Tukiman (Universitas Negeri Medan, 2013)
ABSTRACTAccording to the research world body FAO and WHO health agencies , Enterobacteriaceae that infiltrate the powdered formula causes pain in infants , especially systemic infections such as coughs , colds , pneumonia , and diarrhea necroenterolitis severe that can interfere with growth and development and can disrupt behavior. Immune system disorders are caused by consuming milk formula . The discrepancy could be due to the reaction in the body intersection . Many of the body's organs and systems disruption caused by an allergy to cow's milk . Hypersensitivity to cow's milk protein involving immune system mechanisms . Baby's immune system will fight the protein contained in cow's milk that early symptoms of an allergic reaction will appear . The reaction can occur due to incompatibility of materials contained in the formula such as casein ( milk protein ) , lactose , gluten or certain types of fats . Symptoms due to a mismatch of the formula may appear in fast or slow tempo , can be less than eight hours or more . Signs and symptoms of incompatibility formula or milk allergy is similar to food allergies . The disorder can affect all organs of the body , especially the digestive , skin and respiratory tract. Kata Kunci : Susu formula, kesehatan bayi.